ANALISIS FAKTOR PSIKOLOGIS PENGGUNA BATU AKIK DI KOTA MALANG - Rizki Kurniawan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2015)
This study aims to analysis of the psychological factors the gemstone user in Malang. The research is a qualitative descriptive with phenomenology approach. This approach was chosen because the researchers wanted to examine more about the common experiences of informants while using gemstone. This study uses (6) informant obtained using the snowball of gemstone users who live in Malang. Data collection techniques used is the direct observation, interviews and documentation. Data analysis techniques includes: preparing and reading data, recode, describe coding, narrating themes and interpret the data. The results of studies obtained the following findings. (1) informant has the motivated encouragement external, motivation individual motifs and motivation needs jewelry in using gemstone. (2) the user's perception of gemstone have the notion that by using gemstone one's confidence will increase. (3) learning classified into stimulation impulse (drive) and the stimulation signal (cue) in the use of gemstone. (4) beliefs and attitudes based on three categories: knowledge, feelings and evaluation of the use of gemstone.Keywords: psychological factors, motivation, perception, learning, beliefs and attitudes, phenomenology